Formulation and Physical Evaluation of Hand Sanitizer Gel with Various Concentration Ambon Banana Peel Extract (Musa paradisiaca var. sapientum (L)) - Nastiti, Ginanjar Putri; Rahmayanti, Mayu; Febrian Rezky, Dimas (Journal of Food and Pharmaceutical Sciences, 2024)
Hand washing is an activity that can reduce microorganism contamination, but some people whose work environment is far from hand washing facilities will experience difficulties. This gave rise to the innovation of practical hand washing without water, commonly called a hand sanitizer. Currently, the innovation of materials for making hand sanitizers uses natural ingredients, one of which can be Ambon banana peels, where the use of banana peels can also increase their economic value. The purpose of this study was to evaluate the physical preparation of hand sanitizer gel from Ambon banana peel extract at various concentrations. This study used Ambon banana peels extracted by the UAE method. Next, three hand sanitizer gel formulations were made with the active ingredient, a dry extract of Ambon banana peel. Formulation 1 (F1) uses 7% extract, Formulation 2 (F2) uses 10% extract, and Formulation 3 (F3) uses 13% extract. Each formulation was subjected to physical evaluation, including organoleptic tests, homogeneity, pH, spreadability, and adhesion, for three replications. The results showed that the three formulations had almost the same organoleptic visuals, namely a brown color, a soft texture, and the typical smell of Ambon bananas. Each formulation also fulfills the requirement of being homogeneous, and the pH is within the pH range of the skin. Spreadability and adhesion to the three formulas also meet the requirements for topical preparations. It can be concluded that the three formulations of Ambon banana peel hand sanitizer gel fulfill the requirements as topical preparations based on their physical evaluation. The three formulas did not show significant differences, so the concentration of the active ingredients in this study had no significant effect on the physical state of the preparations